2016
DOI: 10.1183/16000617.0053-2015
|View full text |Cite
|
Sign up to set email alerts
|

Radio(chemo)therapy in locally advanced nonsmall cell lung cancer

Abstract: Definitive radiochemotherapy is the standard treatment for many patients with locally advanced nonsmall cell lung cancer (NSCLC). Treatment outcomes have improved over the last decades. Several treatment regimens have been shown effective and safe. This review summarises the results of significant studies between 1996 and 2015 on concomitant and sequential radiochemotherapy regimens and radiation dose per fraction. Beside therapy regimens, optimised radiotherapy planning is indispensable to improve outcome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…A fourth study included patients treated with RT or CRT [ 24 ]. It was difficult to evaluate the endpoints of this analysis separately for the RT and the CRT cohorts, and in light of the differences in treatment outcomes between RT and CRT [ 29] , that study was also excluded. The data from the remaining three retrospective studies were evaluated in this article [ 26 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A fourth study included patients treated with RT or CRT [ 24 ]. It was difficult to evaluate the endpoints of this analysis separately for the RT and the CRT cohorts, and in light of the differences in treatment outcomes between RT and CRT [ 29] , that study was also excluded. The data from the remaining three retrospective studies were evaluated in this article [ 26 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concurrent chemoradiotherapy is usually the standard treatment for patients with locally advanced NSCLC 24 . However, cases that underwent concurrent chemoradiotherapy were less than the other studies in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, lung cancer is generally divided into small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) (2). NSCLC, including lung squamous cell carcinoma (LSCC) and lung adenocarcinoma (LADC), accounts for ~85% of all lung cancer cases and is the most commonly diagnosed type of lung cancer (2,3). Studies have demonstrated that LADC is overtaking LSCC as the most common histological subtype in various countries, such as the United States and China (4,5).…”
Section: Introductionmentioning
confidence: 99%